Pengembangan Usaha Budidaya Lebah Madu Kelulut pada Kelompok Tani Hutan Tunggal Warga Sukajadi - Sapri; Sari Wahyuni; Sri Rohayu; Gunawan; Rohana; M. Aulia Qodri (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The objectives of this service activity are; 1) Selensen Village is one of the many honey producers in Kemuning District. However, farmers and the community still do not understand the potential of honey, they only sell their harvests that are still raw without being processed first, and 2) Conduct an introduction and management of Bee Honey for farmers so that they can provide a broad understanding so that farmers can developing honey processing. The implementation method is carried out in 2 (two) stages, namely, the method of observation (observation) and interviews, and then the framework of the flow of activities as consideration is carried out for the planned achievements. Based on the results of the service for developing honey bee agricultural potential in Selensen Village, Kemuning sub-district, as well as strengthening the importance of the concept of empowerment in honey bee farming development through a process that involves UNISI students and farmers to ensure the sustainability of bee honey. With the management of bee honey, it is hoped that the income or income of the residents of Selensen Village can grow rapidly and create new innovations for the Selensen Village community to meet the needs and food security in Selensen Village.